Automated detection of individual tree parameters using terrestrial laser scanning data / Mohamad Amirul Hafiz Md Shukri ... [et al.] - Md Shukri, Mohamad Amirul Hafiz; Abd Latif, Zulkiflee; Mohd Zaki, Nurul Ain; Pradhan, Biswajeet; Omar, Hamdan (UiTM Press, 2025)
The National Forest Inventory aims to provide current information on forest resources for planning, management, development, and maintenance purposes, as well as quantitative and qualitative data on forest resources. Although destructive sampling is the most accurate method for obtaining tree information, it requires substantial resources, is time-consuming, and labour-intensive. This study was undertaken to compare the effectiveness of Terrestrial Laser Scanning (TLS) in extracting tree parameters in comparison to conventional methods. The results revealed a strong positive correlation between field-measured Diameter Breast Height (DBH) and manually extracted DBH from TLS point cloud data, with an r value of 1.0 and a Root Mean Square Error (RMSE) of 1.48 cm. However, the relationship between field-measured height and manually extracted height from TLS point cloud exhibited a weak correlation, with an r value of 0.70 and an RMSE value of 7.9 m. In conclusion, TLS data has a significant impact on enhancing the management and monitoring of the inventory status of tropical forests in Malaysia.